2001
DOI: 10.1046/j.1440-169x.2001.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microgravity on the larval development, metamorphosis and reproduction of the urodele amphibian Pleurodeles waltl

Abstract: The FERTILE experiment was twice performed onboard the Mir space station during the Cassiopée and Pégase French space missions. The goal was to analyze the effects of microgravity on fertilization and embryonic development, and then on further development on the ground in the amphibian Pleurodeles waltl. The present paper reports development that occurred in the laboratory after landing. Recovered on the ground at the hatching stage, young larvae reared at room temperature underwent metamorphosis and became ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Yet the larvae that developed had normal morphology and could swim normally [1]. They were later able to mate and reproduce successfully on earth [6]. Other studies that have involved more limited exposure to spaceflight have shown some changes in the development of the vestibular apparatus in the Japanese newt [7] and the vestibuloocular reflex in the African clawed frog (Xenopus) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Yet the larvae that developed had normal morphology and could swim normally [1]. They were later able to mate and reproduce successfully on earth [6]. Other studies that have involved more limited exposure to spaceflight have shown some changes in the development of the vestibular apparatus in the Japanese newt [7] and the vestibuloocular reflex in the African clawed frog (Xenopus) [8].…”
Section: Introductionmentioning
confidence: 99%
“…however, the embryos demonstrate the ability to compensate for nervous system abnormalities [35]. From video taken on board the MIR space station, it was clearly that embryos with such abnormalities developed into hatched larvae [31]. Thus, those abnormalities were temporary and subsequently reversible, and outside several acephalic and microcephalic specimens, ontogeny proceeded quite normally for microgravity-exposed embryos.…”
Section: Spanish Ribbed Newtmentioning
confidence: 99%
“…In general, effects observed in anuran amphibian species were dependent on the developmental stages at which the animals were launched and on the rearing devices used during the space flights [31].…”
Section: Anuran Amphibian Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Female of P. waltl lays fertilized eggs like other urodeles (internal fertilization). Since the female newts keep the sperm for several months after mating, we could obtain fertilized eggs without males (Dournon et al 2001). Eggs obtained just after fertilization were required for efficient transgenesis; however, it is difficult to determine the exact timing of fertilization when it occurs internally.…”
Section: Artificialmentioning
confidence: 99%